2016
DOI: 10.1177/0040517516632475
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of PSA/PEDOT conductive composite yarns

Abstract: Polysulfonamide/poly(3,4-ethylenedioxythiophene) (PSA/PEDOT) conductive composite yarns were prepared by the vapor phase polymerization technique. Ferric chloride (FeCl3) was used as the oxidant initiator with five different concentration settings (20, 40, 60, 80, and 100 g/L). The effects of oxidant concentration on the chemical composition, mechanical properties, and electrical conductivity of PSA/PEDOT composite yarns were analyzed. The surface resistance and mass-specific resistance of conductive yarns wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The FTIR measurement was carried out at a wavenumber ranging from 400 to 4000 cm –1 (Figure a). The characteristic absorption peak positions of composites at 1612, 1385, 1136, 1098, and 969 cm –1 correspond to the result of pure PEDOT in the inset pattern (1523, 1366, 1214, 1090, and 980 cm –1 , respectively) with some slight shift, which matched well with previous reports. The vibration absorption peak at 1612 cm –1 was assigned to the asymmetrical CC stretching vibration because of conjugation, indicating a high conductivity. , The absorption bands observed at 3415 and 2838 cm –1 belonged to the asymmetrical stretching vibration, symmetrical stretching vibration. FTIR spectra of the samples after removing the PEDOT show the Fe–O bond stretching at 567 and 476 cm –1 , suggesting the existence of Fe 2 O 3 in PEDOT-IE-Fe 2 O 3 .…”
Section: Resultssupporting
confidence: 88%
“…The FTIR measurement was carried out at a wavenumber ranging from 400 to 4000 cm –1 (Figure a). The characteristic absorption peak positions of composites at 1612, 1385, 1136, 1098, and 969 cm –1 correspond to the result of pure PEDOT in the inset pattern (1523, 1366, 1214, 1090, and 980 cm –1 , respectively) with some slight shift, which matched well with previous reports. The vibration absorption peak at 1612 cm –1 was assigned to the asymmetrical CC stretching vibration because of conjugation, indicating a high conductivity. , The absorption bands observed at 3415 and 2838 cm –1 belonged to the asymmetrical stretching vibration, symmetrical stretching vibration. FTIR spectra of the samples after removing the PEDOT show the Fe–O bond stretching at 567 and 476 cm –1 , suggesting the existence of Fe 2 O 3 in PEDOT-IE-Fe 2 O 3 .…”
Section: Resultssupporting
confidence: 88%
“…The relation between the temperature of fabric and the voltage applied was investigated, which can be used for practical heated temperature prediction. The effects of voltage on the electrothermal properties of twin polymer, conductive composite yarns were reported by Yu et al 26 The maximum heating temperature of yarns could be rapidly increased with an increase of applied voltage and then tended to be stable. The heating properties of a stretchable and flexible strip-shaped, thermochromic resistive heater (TRH) fabricated by incorporating an aligned carbon nanotube sheet and thermochromic silicone elastomer were investigated by Li et al 13 The TRH textiles demonstrated rapid thermal response and high stability even under various deformations, such as stretching, twisting, etc.…”
mentioning
confidence: 79%
“…Examples of conductive materials include gold [17], silver [18], nickel [19], conductive polymers, such as poly (3,4-ethylenedioxythiophene): poly (styrene sulfonate) [20], and carbonized materials, such as carbon nanotubes [21], graphene [22], graphite [23], and carbon black [24]. Among these materials, conductive textiles made with coated micro-or nano-scaled metal particles achieve an extremely low resistivity (less than 1 × 10 −7 Ω•m [25]) when compared with carbonized materials and conductive polymers, but they require complex processes, such as metal particle synthesis and/or purification.…”
Section: Justification Of the Conductive Materialsmentioning
confidence: 99%
“…Examples of polymer binders include polyaniline [21], polyamide [30], polypyrrole [19], and polyurethane [15]. Examples of additive agents are sodium/cetyltrimethyl ammonium bromide [20] and the anionic wetting and dispersing agent DELTA-DC 4242 [31]. The binder and agent are used to formulate a uniform and stable carbon black paste by using an appropriate solvent.…”
Section: Justification Of the Binder Materials Selectionmentioning
confidence: 99%